The Linguistic Relativity Hypothesis of the Holy Quran - Varzandeh, Mohsen (Contemporary Quran, 2022)
Given the interaction between language and thought, this novel work proposes a linguistic relativity hypothesis of the Holy Qur’an. Supported with evidence from thorough investigation of Sapir-Whorf’s Linguistic Relativity Hypothesis, and linguistic characteristics unique to this divine book ranging from surface structure to deep structure, especially its semantic layers, the proposed hypothesis states that the linguistic structure of the Holy Quran influences and shapes the reader's thought. In the meantime, convergent thinking and divergent thinking emerge as two directions of thought, respectively. The language of the Holy Qur’an influences, shapes and directs one’s thought about himself/herself and the universe.